2007
DOI: 10.1111/j.1365-2621.2006.01294.x
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and organoleptic characteristics of Uapaca kirkiana, Strychnos cocculoides, Adansonia digitata and Mangiferia indica fruit products

Abstract: Uapaca kirkiana ('Masuku') and Strychnos cocculoides ('Kabeza') juices and jams as well as juices from Adansonia digitata (Baobab, 'Malambe') and Mangifera indica (mango) were prepared, evaluated by a trained ten-member panel (seven women and three men) and analysed for their physicochemical and shelf-life characteristics. The physicochemical data indicated that juices and jams are rich sources of zinc, copper and phosphorus. While sensory evaluations of the jams were not significantly different between Uapaca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 7 publications
6
50
0
1
Order By: Relevance
“…Saka et al (27) reported a mean acidity of 1.13% for S. cocculoides processed juice. The relatively high acidity of Strychnos spp.…”
Section: Taste and Texturementioning
confidence: 99%
See 4 more Smart Citations
“…Saka et al (27) reported a mean acidity of 1.13% for S. cocculoides processed juice. The relatively high acidity of Strychnos spp.…”
Section: Taste and Texturementioning
confidence: 99%
“…Strychnos cocculoides jam was highly scored by consumers, also because of its taste, (29) and in general consumer acceptance of the other monkey orange fruit products was high in literature surveyed. (9,27,29) All in all, the sensory studies indicated the potential for product development and commercialization of the species.…”
Section: Taste and Texturementioning
confidence: 99%
See 3 more Smart Citations